Factors affecting decisions to invest in Fruit production - Mohayidin, Mohd Ghazali (Universiti Kebangsaan Malaysia, 1985)

(untitled)
Agricultural policies to induce small farmers to increase fruit production were initiated and formalized as early as 1961, when it was realized that appoximately 82 per cent of the fruit acreage needed replanting or rehabilitation. Assistance to the farmers was given in the form of subsidized approved planting materials, fertilizers, and some essential equipment. However, the program itself remained practically stagnant until 1972, when the government increased the amount of financial assistance substantially. The amount of financial assistance given was again raised in 1976. Tariffs on imported fruits were imposed and other fiscal measures were deployed in the effort to stimulate the growth and development of the fruit industry. Among the important steps taken to promote local fruit production were the establishment of goverment agencies such as the Food Industries of Malaysia (FIMA) and the Federal Agricultural Marketing Authority (F AMA).